PENINGKATAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PRAKTIS PADA MATERI SHOLAT DAN ZIKIR - Mira Susanti; Zulfani Sesmiarni; Rodi; Mutammimul Hayati; Zukfikri (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study aims to improve the learning outcomes of grade VII students through a practical approach to prayer and dhikr material. In this study, the learning methods applied include demonstrations, simulations, and group discussions, so that students are actively involved in the practice of worship. For six weeks, students were trained to understand the procedures for prayer and dhikr with a focus on direct experience. Data were collected through pre- and post-learning tests, as well as observations of student participation in class. The results of the analysis showed an increase in the average test score from 68 to 86, as well as an increase in student motivation and activeness as reflected in the questionnaire. In addition, students showed a beter understanding of the meaning and purpose of worship. These findings emphasize the effectiveness of a practical approach in religious learning, which can shape students' character and discipline in worship. This study recommends the application of similar methods in various educational contexts to improve religious learning outcomes.